Light condition on the biometry and germination of dispersal units of Cordia ecalyculata - Cossa, Conceicao Aparecida; Lima, Cristina Batista de; Fonseca Sorace, Maria Aparecida da; Janani, Jamile Kassem [UNESP]; Bonato Negrelle, Raquel Rejane (Univ Estadual Centro-oeste, 2015)
The aim of this study was to explore the biometric characteristics of the dispersal units (fruits, pyrenes and seeds), germination and the effect of treatments for overcoming the dormancy of Cordia ecalyculata seeds, produced under different natural light conditions. We used ripe fruits with red coloration, collected from main trees, located in different areas regarding natural light. We determined the biometry of fruits and pyrenes. The pyrenes were exposed to different treatments for the scarifying of the seed coat. The seeds were analyzed as for imbibition, viability and germination, after being subjected to treatments for dormancy overcoming. The natural light conditions influenced the biometric parameters of the fruits, pyrenes and seeds, whose dimension varied according to the availability of solar light of the place where the mother plant was located. The germination percentage and the incidence of seeds without embryos were inversely proportional to the shading. The treatments employed did not affect satisfactorily on the overcoming of dormancy of C. ecalyculata seeds.
Keywords: porangaba; tetrazolium; scarifying; seed viability